Chaotic global parameters correlation with heart rate variability in obese children - Vanderlei, Franciele M. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Garner, David M. (Faculdade de Filosofia e Ciências, 2014)
The aim of the study is to analyze heart rate dynamics in obese children by measures of HRV. HRV is a simple and non-invasive measure of autonomic impulses. 94 children of mixed gender aged eight to twelve years were divided into two equal groups based on body mass index: obese and normal weight range. HRV was monitored in the dorsal decubitus position for 20 minutes. After tests of normality, Kruskal Wallis was applied for the statistical analysis, with the level of significance set at (p < 0.05). Regarding the application of Principal Component Analysis the first two components represent 99.4% of total variance. The obese children exhibited in heart frequency dynamics associated to an increase in the Chaos Forward Parameter. The Chaos Forward Parameter which applies all three chaotic global parameters is suggested to be the most robust algorithm. Obesity in children can be termed a dynamical condition but it increases the chaotic response.
Keywords: Electrocardiography; Nonlinear dynamics; Principal component analysis